2020
DOI: 10.3390/educsci10060150
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduates Interested in STEM Research Are Better Students than Their Peers

Abstract: In Science, Technology, Engineering, and Mathematics (STEM), undergraduate research experiences provide students with invaluable opportunities to improve scientific skills. However, less is known about its impact on higher-order thinking skills. Therefore, we sought to determine if engagement in undergraduate research would improve academic performance in students engaged in research compared to those that were not. To accomplish this, biology majors were enrolled in courses that taught research methodology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…To register any research project with the university's ethics and research committees, the proposal must include at least one professor, one postgraduate student (clinical resident, master's, or Ph.D. student), and one medical student. Similar models and interventions have been described as successful in the nursing education literature (Moch et al, 2010;Feldman et al, 2013;Niven et al, 2013;Jansen et al, 2015;Coyne et al, 2018) and other health science fields (Grevholm et al, 2005;Bickford et al, 2020). This initiative has helped more students get involved and participate with presentations in medical meetings or publications, however, future studies will be necessary to evaluate the efficacy of this modality.…”
Section: Discussionmentioning
confidence: 84%
“…To register any research project with the university's ethics and research committees, the proposal must include at least one professor, one postgraduate student (clinical resident, master's, or Ph.D. student), and one medical student. Similar models and interventions have been described as successful in the nursing education literature (Moch et al, 2010;Feldman et al, 2013;Niven et al, 2013;Jansen et al, 2015;Coyne et al, 2018) and other health science fields (Grevholm et al, 2005;Bickford et al, 2020). This initiative has helped more students get involved and participate with presentations in medical meetings or publications, however, future studies will be necessary to evaluate the efficacy of this modality.…”
Section: Discussionmentioning
confidence: 84%
“…It has also been widely recognized that personal interactions between research mentors and undergraduate students (the interactions via mentored research, research courses, working in a lab) have positive influences on undergraduate students' maturation, the overall education experiences. It has been shown that engagement in undergraduate STEM research would improve academic performance in students engaged in research compared to those who were not [22]. To evaluate the overall student experience of the undergraduate research experiences and CUR-TP project, a voluntary survey (see the Survey in the Supporting Information) was administered to the research students at the end of the semester.…”
Section: The Importance Of Undergraduate Research-the Students' Perspectivesmentioning
confidence: 99%
“…The term "open schooling" emerged in 2015 in the report promoted by the European Union "Science Education for Responsible Citizenship" (HAZELKORN et al, 2015), which highlights the role of science, including scientific skills as a central axis in educating young people to investigate, intervene and innovate in a responsible and responsive way. Students' scientific skills provide students with invaluable opportunities to improve their lifelong learning, academic performance, confidence and interest in STEM careers (BICKFORD et al, 2020).…”
Section: Open Schooling For Professional Educationmentioning
confidence: 99%